The Influence of The Independent Learning System on Student Achievement in The Medical Education Program - Henny Tambingon; Shelty Sumual; Orbanus Naharia (Green Publisher Indonesia, 2024)
The Indonesian government launched the Independent Campus Learning (MBKM) policy in 2020. This policy aims to provide greater autonomy to universities and students in designing learning that is innovative and in line with the needs of the times. The aim of this research is to determine the influence of the Merdeka Belajar system on student achievement in the medical education study program. This research uses quantitative research methods. Data was collected through surveys using questionnaires and literature studies. The data that has been collected is then analyzed using a regression test using the SPSS program. The research results show that there is a significant influence between the MBKM system on the achievement of students in the Medical Education study program. The group of students who took part in the MBKM program showed higher learning achievement compared to the group of students who did not take part in the MBKM program. This program provides students with the opportunity to learn and develop more optimally, thereby producing graduates who are more qualified and ready to face the challenges of an increasingly complex world of work.